To study the effect of early versus late trophic feeding in preterm neonates with mild respiratory distress syndrome - Sinha, Rahul; Venkatnarayan, K; Dalal, Shamsher; John, B M; Syed, V Sabid (Indian Journal of Child Health, 2016)
Background: The respiratory distress syndrome in preterm neonates is mostly due to surfactant deficiency. The incidence and severity of respiratory distress syndrome are related inversely to the gestational age of the newborn infant. The early nutritional support, in these preterm neonates with respiratory distress, prevents complications, and maintains positive energy balance. Objective: The aim was to study the effect of early versus late trophic feeding in preterm neonates with mild respiratory distress syndrome. Materials and Methods: This was a prospective study conducted in babies admitted to neonatal intensive care unit (NICU) from January 2013 to January 2016 in Military Zonal Hospital. A total of 200 babies with a gestational age <37 weeks and birth weight between 1200 and 2000 g were evaluated and divided into the early and late group. In early group, the nutritional support in the form of expressed breast milk 15 ml/kg/day in preterm neonates with mild respiratory distress was given within 24 h of life and in late group after 48 h of life. Results: The early nutritional support in preterm neonates with mild respiratory distress decreases the requirement of oxygen and caffeine, helps to reach early full feeds, decrease in the incidence of necrotizing enterocolitis, early weight gain and early discharge from hospital. Conclusion: In our study findings, certainly suggest the benefits of early trophic feed compared to late in preterm neonates with mild respiratory distress. It seems that better education of mothers for expressing their milk and handing to NICU for use in trophic feeding is important. However the large randomized controlled trial is required to validate the above findings.